English Teaching Based-Strategy LMS Moodle and Google Classroom: Feature of Testing and Feedback - Prasetya, Rizky (Universitas Nusantara PGRI Kediri, 2021)
Teaching English Foreign Language (TEFL) has shifted complex for developing countries, especially Indonesia. Pandemic conditions bound conventional face-to-face teaching. A virtual classroom is another way of implementing the learning and teaching process. The purpose study investigates and describes the selection of English teaching based-strategy LMS Moodle and Google Classroom, particularly the testing and feedback feature. The qualitative research approached grounded theory. The entire data was collected by the questioner using purposeful sampling. The testing teaching strategies LMS Moodle discovered multiple-choice, short answer, essay, true/false statement, and missing word. Even though testing teaching strategies, Google Classroom was found multiple-choice, short answer, and essay. The selection of assessments is one of the benchmarks for English lecturers' readiness to teach using Moodle and Google classroom media. The testing variety is capable of encouraging students to perform well in e-learning. Feedback selection classifications were discovered, formal feedback, formative feedback, and summative feedback. Formal feedback is designed and regularly scheduled for the process. Formal feedback is designed and regularly scheduled for the process. The formative feedback is to observe student learning to provide continuous feedback. The summative testing evaluates student learning at the end of an instructional unit by comparing it against some patterns